Response of Phaseolus vulgaris to the Use of Growth-Promoting Microorganisms Associated with the Reduction of NPK Fertilization in Tropical Soils: Clayey Oxisol and Sandy Ultisol - Loiane Fernanda Romão de Souza; Nelson Câmara de Souza Júnior; Guilherme Carlos Fernandes; William Cesar Nishimoto Ito; Mariana Cristina Barbosa; Leilane Bernardes Freitas; Karina da Silva Souza; Lidiane dos Santos Alexandre; Mariana Bonini Silva; Edson Cabral da Silva; Orivaldo Arf; Marlene Cristina Alves; et al. (Agriculture)
This research analyzed the effects of inoculation with Rhizobium tropici, combined with beneficial microorganisms, on the reduction of NPK fertilization and its impacts on common beans. Conducted in two types of soil (clayey Oxisol and sandy Ultisol), the experimental design was a randomized block design under a factorial scheme 4 × 4, with different combinations of inoculation (Rhizobium tropici alone or in combination with Azospirillum brasilense, Bacillus subtilis, and Trichoderma harzianum) and fertilization doses (0%, 33%, 66%, and 100% of the recommended dose). The results showed that inoculation with R. tropici, especially in combination with Trichoderma harzianum, increased nodule formation and improved agronomic parameters such as leaf chlorophyll, dry matter of the plant, number of pods, and grains. Co-inoculation with Azospirillum brasilense resulted in a significant increase in grain yield, particularly in clayey soil with 33% NPK. Inoculation with lower doses of NPK was sufficient for good yield, suggesting the feasibility of reducing the use of mineral fertilizers. This study indicates that soils with corrected fertility, in a no-tillage system, can contribute to the reduction of fertilizer use due to the cycling of organic matter and improvement of soil health. Additionally, the use of microorganisms is an effective ally for the sustainability of agroecosystems.